Drug-eluting stents Versus Coronary Artery Bypass Grafting in Multivessel Disease and Left Main Obstruction: Meta-analysis of Randomized Clinical Trials - Andrade,Pedro José Negreiros de (2018)
Abstract Background: The choice between percutaneous coronary intervention (PCI) and coronary artery bypass grafting (CABG) remains controversial. Objective: To conduct a meta-analysis of randomized studies comparing drug-eluting stents (DES) and CABG in multivessel disease or obstruction of the left main coronary artery. Method: Electronic databases were searched systematically to evaluate results of randomized trials comparing PCI with DES versus CABG in multivessel disease and obstruction of the left main coronary artery. Ten studies were identified. Results: In the aggregated results (n = 9268), mortality at 30 days and incidence of stroke favored PCI (0.8% versus 1.5%, p = 0.005; 0.4% versus 1.5%, p < 0.0001, respectively). There was no difference in mortality at 1 year (3.4% versus 3.5%, p = 0.50). The late mortality favored CABG (10.1% versus 8.5%, p = 0.01). In patients with diabetes derived from four studies (n = 3830), late mortality favored CABG (12.5% versus 9.7%, p < 0.0001). In six studies of left main coronary artery obstruction (n = 4700), the incidence of stroke favored PCI (0.3% versus 1.5%, p < 0.001) and there was no difference in mortality at 30 days (0.8% versus 1.3%, p = 0.15), mortality at 1 year, or late mortality (8.1% versus 8.1%). The subgroups with high SYNTAX score and diabetes were those influencing most strongly and adversely the PCI results. Conclusion: When compared with PCI, CABG was superior in regards to late mortality and inferior in regards to 30-day mortality and incidence of stroke. Diabetes and SYNTAX score strongly impacted the results.